Analysis of carbon-abatement investment for thermal power market in carbon-dispatching mode and policy recommendations. (15th April 2018) - Zhang, Xinhua; Yang, Hongming; Yu, Qian; Qiu, Jing; Zhang, Yongxi
Abstract: In this paper, we present a framework that aims to minimise power generation costs while satisfying carbon emission constraints. We then construct a carbon-abatement investment-option game model for asymmetric generation companies. The results show that the investment behavior of generation companies is largely affected by the critical value of the electricity price after carbon-abatement investment (relative decarbonization price). When the relative decarbonization price is lower than the critical value, only generation companies with low emission are motivated to invest in carbon abatement. By contrast, companies with high emission will only make such investments when the relative decarbonization price is higher than the critical value. We find that raising the proportion of competitive electricity will stimulate generation companies to invest in carbon abatement, while the influence of carbon-emission targets on investment behavior is uncertain. Compared with implementing a subsidy, increasing the relative decarbonization price can motivate generation companies to invest in carbon abatement more effectively. Highlights: Present a framework that helps to reduce power generation emissions at minimum cost. Build an asymmetric carbon-abatement investment-option game model. Carbon-abatement investment thresholds in the duopoly market are analyzed. Policies that stimulate plants to invest in carbon-abatement can be obtained.